2017
DOI: 10.1093/conphys/cox010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ambient oxygen and size-selective mortality on growth and maturation in guppies

Abstract: Human activities, e.g. nutrient enrichment (resulting in low oxygen) and selective fishing (i.e. higher mortality of large fish), affect growth and maturation (key characteristics determining fish life history). We investigated combined effects of oxygen and size-dependent mortality on growth and maturation to provide informed management decisions for these events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 72 publications
2
19
0
Order By: Relevance
“…Baulier et al () found that male (and, to a lesser extent, female) reproductive allocation increased during periods of high fishing mortality in Atlantic cod ( Gadus morhua ). Moreover, results from a size selection experiment on guppies suggest that changes in reproductive allocation were particularly evident in males, but not in females (Diaz Pauli, Kolding, Jeyakanth, & Heino, ). Thus, the enhanced reproductive performance of the large‐harvested line is likely caused by the evolution of a fast life history that increased fecundity in females (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Baulier et al () found that male (and, to a lesser extent, female) reproductive allocation increased during periods of high fishing mortality in Atlantic cod ( Gadus morhua ). Moreover, results from a size selection experiment on guppies suggest that changes in reproductive allocation were particularly evident in males, but not in females (Diaz Pauli, Kolding, Jeyakanth, & Heino, ). Thus, the enhanced reproductive performance of the large‐harvested line is likely caused by the evolution of a fast life history that increased fecundity in females (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a number of experimental studies and field observations do show a negative relationship between water oxygen concentration and ectotherm body sizes, both in fish and invertebrates. Guppies reared at 65% air saturation (i.e., 65% of normoxia) matured earlier and had stunted growth (Diaz Pauli, Kolding, Jeyakanth, & Heino, ), and growth rate was also negatively correlated with oxygen concentration in tilapia, when fish were reared at c . 20%, 35% and 75% of air saturation conditions (such oxygen concentrations do occur in natural tilapia habitats; Kolding, Haug, & Stefansson, ).…”
Section: Are Aquatic Organisms Limited By Their Capacity To Uptake Oxmentioning
confidence: 99%
“…Nevertheless, a number of experimental studies and field observations do show a negative relationship between water oxygen concentration and ectotherm body sizes, both in fish and invertebrates. Guppies reared at 65% air saturation (i.e., 65% of normoxia) matured earlier and had stunted growth (Diaz Pauli, Kolding, Jeyakanth, & Heino, 2017), and growth rate was also negatively correlated with oxygen concentration in tilapia, when fish were reared at c. 20%, 35% and 75% of air saturation conditions (such oxygen concentrations do occur in natural tilapia habitats; F I G U R E 1 A simplified representation of possible and not exclusive mechanisms explaining the empirically observed phenomenon (top right) of decreasing ectotherm body sizes with increasing temperature. Blue symbols and lines indicate processes at lower temperature, while red indicates the same processes at higher temperature.…”
Section: Are Aquati C Org Anis Ms Limited By Their C Apacit Y To Upmentioning
confidence: 99%
“…Next to maturation schedules, harvesting selection also acts on somatic growth rates yb removing large-bodied individuals at a given age, thus favouring slow-growing genotypes. However, if the strength of selection for earlier maturation overwhelms the strength of selection for slower somatic growth, harvesting may favour the evolution of faster growth rates, as these allow an earlier maturation (Dunlop et al 2009, Eikeset et al 2016, Diaz Pauli et al 2017 . In these instances, evolution is entirely driven by the direct effects of the harvesting process.…”
Section: Eefl-absent Dynamicsmentioning
confidence: 99%